Kewenangan dan Tanggung Jawab Notaris dalam Pembuatan Akta Pendirian Perseroan Terbatas Menurut Undang-Undang Jabatan Notaris (UUJN) dan Undang-Undang Perseroan Terbatas (UUPT): The Authority and Responsibility of Notaries in Drafting Deeds of Establishment of Limited Liability Companies under the Notary Office Act (UUJN) and the Limited Liability Company Act (UUPT) - Sofya Mahira; Arif Rahman; Fatahillah (Jurnal Kolaboratif Sains, 2026)
Proses pendirian Perseroan Terbatas memerlukan peran Notaris sebagai pejabat umum yang berwenang membuat akta autentik. Dalam praktiknya, masih ditemukan permasalahan akibat pelanggaran prosedur jabatan maupun pemberian keterangan yang tidak sesuai dengan keadaan sebenarnya oleh para penghadap sehingga menimbulkan sengketa hukum yang melibatkan Notaris. Penelitian ini bertujuan menganalisis kewenangan dan tanggung jawab Notaris dalam pembuatan akta pendirian Perseroan Terbatas berdasarkan Undang-Undang Jabatan Notaris dan Undang-Undang Perseroan Terbatas, serta mengkaji bentuk pertanggungjawaban dan akibat hukum apabila akta yang dibuat mengandung cacat hukum. Penelitian ini menggunakan metode hukum empiris dengan pendekatan kualitatif. Data primer diperoleh melalui wawancara dengan Notaris dan anggota Majelis Pengawas Daerah Kota Medan, sedangkan data sekunder berasal dari peraturan perundang-undangan dan literatur hukum. Seluruh data dianalisis secara deskriptif untuk mengidentifikasi kesenjangan antara ketentuan normatif dan praktik kenotariatan. Hasil penelitian menunjukkan bahwa kewenangan Notaris dalam pendirian Perseroan Terbatas berlandaskan Pasal 15 ayat (1) Undang-Undang Nomor 2 Tahun 2014 tentang Jabatan Notaris dan Pasal 7 ayat (1) Undang-Undang Nomor 40 Tahun 2007 tentang Perseroan Terbatas. Notaris juga berperan memberikan penyuluhan hukum guna mencegah sengketa. Apabila terjadi pelanggaran, Notaris dapat dimintai pertanggungjawaban administratif, perdata, maupun pidana sesuai dengan ketentuan peraturan perundang-undangan. Cacat hukum pada akta dapat mengakibatkan akta autentik kehilangan kekuatan pembuktian sempurna dan hanya bernilai sebagai akta di bawah tangan. Oleh karena itu, Notaris perlu meningkatkan ketelitian dalam verifikasi dokumen dan pelaksanaan prosedur jabatan. Di sisi lain, pengawasan oleh Majelis Pengawas Daerah perlu diperkuat, serta masyarakat harus bertanggung jawab atas kebenaran data yang diberikan agar tercipta kepastian hukum dalam pendirian Perseroan Terbatas. ABSTRACT The establishment of a Limited Liability Company (Perseroan Terbatas) requires the role of a Notary as a public official authorized to prepare authentic deeds. In practice, legal issues continue to arise due to non-compliance with statutory procedures or the submission of inaccurate information by the appearing parties, thereby involving Notaries in legal disputes. This study aims to analyze the authority and responsibilities of Notaries in preparing deeds of establishment for Limited Liability Companies under the Law on Notarial Office and the Company Law, as well as to examine the forms of legal liability and legal consequences arising from defects in such deeds. This research employs an empirical legal method with a qualitative approach. Primary data were obtained through interviews with Notaries and members of the Regional Supervisory Council (Majelis Pengawas Daerah) in Medan City, while secondary data were collected from statutory regulations and relevant legal literature. The data were analyzed descriptively to identify the gap between normative legal provisions and notarial practice. The findings indicate that the authority of a Notary in establishing a Limited Liability Company is based on Article 15 paragraph (1) of Law Number 2 of 2014 concerning the Notarial Office and Article 7 paragraph (1) of Law Number 40 of 2007 concerning Limited Liability Companies. In practice, Notaries also provide legal counseling to prevent potential disputes. Where violations occur, Notaries may incur administrative, civil, or criminal liability in accordance with the applicable laws and regulations. A legally defective deed may lose its status as an authentic deed and be reduced to the evidentiary value of a private deed, thereby diminishing its legal certainty. Therefore, Notaries are expected to exercise greater diligence in verifying documents and complying with statutory procedures. Furthermore, the supervisory function of the Regional Supervisory Council should be strengthened, while the public should ensure the accuracy of the information provided to Notaries in order to uphold legal certainty in the establishment of Limited Liability Companies.